An overview on the use of unmanned aerial vehicles for medical product transportation: flight dynamics and vibration issues - Geronel, Renan S. [UNESP]; Begnini, Guilherme R.; Botez, Ruxandra M.; Bueno, Douglas D. [UNESP] (Springer Nature, 2022)
Advances in technology and the possibility to carry different sensors and payloads have led to the increasing use of unmanned aerial vehicles (UAVs) by the medical sector. Currently, the use of UAVs for medical goods transportation is restricted to a few areas spread all over the world. However, UAVs have been gaining popularity since they became cheap, reliable, and able to overcome geographical and economical challenges, related to poor infrastructure or remote areas. Depending on the intensity and amplitude of the vibration at which a UAV is subjected to, several complications can arise, such as decrease in equipment reliability, reduction of fatigue life, inaccurate information from measurement tools, and a decrease in the quality of the transported load. This article presents a literature review on the use of UAVs for medical transportation, by focusing on the evaluation of the vibration impact on medical product integrity. In order to understand the vibration characteristics caused by rotational components, maneuvers and environmental disturbances, some flights were performed with a quadcopter carrying a payload using different attachment configurations. The vibration levels of the aerial vehicle and its payload were assessed and a significant amplification of the vibration levels of the UAV payload was found for all configurations, indicating the importance of the correct attachment design for medical transportation.
Keywords: Medical product transportation; Payload integrity; Time-varying acceleration; Unmanned aerial vehicles; Vibrations effects